2017
DOI: 10.1155/2017/1597463
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Total Hip Replacement in Patients with Parkinson’s Disease: Comparison of the Elective and Hip Fracture Groups

Abstract: Introduction The aim of the study was to compare the clinical outcomes following elective and traumatic total hip arthroplasty in Parkinson's disease patients. Materials and Methods Ten patients with osteoarthritis comprise the elective group (mean age at operation 74 years; mean follow-up 82 months). Thirteen patients with femoral fracture comprise the hip fracture group (mean age 76 years; mean follow-up 54 months). All patients were followed up at 6 and 36 months postoperatively and at the time of the lates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 34 publications
(45 reference statements)
0
30
0
Order By: Relevance
“…The majority of studies have demonstrated that THA and TKA are safe in patients with Parkinson's disease and achieve excellent pain control [16][17][18][19]. Functional outcomes are less clear, but longer term are likely related at least in part to disease progression [13,14,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies have demonstrated that THA and TKA are safe in patients with Parkinson's disease and achieve excellent pain control [16][17][18][19]. Functional outcomes are less clear, but longer term are likely related at least in part to disease progression [13,14,39].…”
Section: Discussionmentioning
confidence: 99%
“…The literature on THA and TKA outcomes in PD patients is largely limited to case series of operations performed between the 1970s and 1990s [11][12][13][14][15]. Of the larger studies that have been done, all demonstrated that PD patients experienced relief of pain, the most common reason for surgery, but changes in functional status were less consistent [16][17][18][19]. Studies of perioperative complications associated with TKA and THA have suggested that comorbid PD is associated with increased rates of perioperative urinary tract infection, cognitive dysfunction, blood transfusion, periprosthetic infection, hip fracture, or dislocation [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Meanwhile, PD patients are living longer and with progressively improving medical treatment enabling them to maintain greater functional status long-term, PD patients can be considered for both elective hip arthroplasty as well as arthroplasty as a treatment for fracture. 10 Previously, PD has been considered a contraindication to both total knee (TKA) and total hip arthroplasties (THAs). 7,11 Patients with PD have reportedly experienced higher rates of medical complications than those among the general population.…”
Section: Introductionmentioning
confidence: 99%
“…12 Early studies also demonstrated high postoperative mortality following arthroplasty in PD patients, suggesting increased dislocation rates with uncertain long-term functional gains. 7,10 However, recent studies have suggested that both hip and knee arthroplasty provide excellent long-term pain relief, with dislocation rates likely comparable to that of the general population. 1,5,7,10,[13][14][15][16] Dislocation rates after THA are reported to range between 0.2 and 2% in the general population, and anywhere from 0 to 37% in PD patients, with 1 standardised review finding no difference in outcomes from patients without PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation